Mosquito Species Classification Using Wingbeat Acoustic Signals Based on Bidirectional Long Short-Term Memory - Dwifani, Bella Melati Wiranur; Kasyidi, Fatan; Ilyas, Ridwan (Jurnal Teknik Informatika (Jutif), 2025)
The increasing prevalence of mosquito-borne diseases such as Dengue, chikungunya, and malaria underscores the urgent need for effective mosquito vector monitoring. This study proposes a non-invasive classification system of mosquito species based on wingbeat acoustic signals using a deep learning approach with Bidirectional Long Short-Term Memory (BiLSTM). The audio dataset was collected from the Wingbeats repository, consisting of six major mosquito species. Preprocessing was performed using Discrete Wavelet Transform (DWT) to reduce noise. Feature extraction combined Linear Predictive Coding (LPC) and Mel-Spectrogram to represent spectral and temporal signal characteristics. Each binary model was trained in a one-vs-rest scheme to recognize a target species against others, and a BaggingClassifier was used to fuse predictions from six BiLSTM models. Evaluation showed that the proposed system achieved a final accuracy of 96.85% and F1-score of 95.03%, with confusion matrices showing near-diagonal performance. The results indicate that the hybrid LPC-Mel features and ensemble BiLSTM architecture are effective for mosquito species classification using acoustic signals.